Characterization of netB positive Clostridium perfringens Type A Recovered from Necrotic Enteritis in Commercial Broiler Flocks - Balam, Deepthi; Maddireddy, Himaja; Moturi, Srivani; Kumari P, Mohini (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Necrotic enteritis (NE) is a significant GI tract disease in chickens, predominantly caused by type A strains of Clostridium perfringens. This condition presents a substantial financial burden on the farmers, jeopardizing flock health and productivity. Recent research highlights the crucial role of the netB toxin, as a primary pathogenic factor in the development of NE. Present study details an outbreak of NE recorded in a commercial broiler flock raised in deep litter system. Dead birds were presented for necropsy with a history of sudden heavy mortality. Significant pathological features in the intestines and viscera of the affected birds were suggestive of NE. Microbiological evaluation including cultural examination and molecular characterization targeting 16s rRNA sequences revealed presence of C. perfringens. Toxinotyping of the isolate under study revealed that the predominant toxin produced was alpha toxin and that it belongs to C. perfringens type A. The isolate was also found to produce netB toxin. Heavy mortality recorded in the present investigation may be attributed to netB gene.